Perancangan Layout Card Game Edukasi Tentang Hewan Langka di Indonesia - Steven; Restu Ismoyo Aji; Pungky Febi Arifianto (UNIVERSITAS STEKOM, 2026)
This study aims to design a card layout for an educational card game about endangered animals in Indonesia. The research uses qualitative and quantitative methods, including observation, interviews, literature study, and questionnaires. The design process involves identifying information needs, developing layout structures, and producing several design alternatives. The results show that the selected layout has good readability, clear information hierarchy, and an appealing visual composition based on respondent evaluation. The arrangement of visual elements such as illustration, typography, and icons is structured systematically to enhance user understanding. Thus, the card layout functions not only as an aesthetic element but also as an effective visual communication medium in supporting interactive learning.